Cohort case series of swine flu cases admitted to hospital - Rao, Bhavana Venkata Nagabhushana; Raman, Bhavana Venkata Satya (International Journal of Research in Medical Sciences, 2017)
Swine flu is a disease of great concern but warrants no panic. General public and some medical professionals consider Swine flu as highly fatal disease with universal mortality. We present here ten cases of category C Swine flu cases admitted during a period of one month with good outcome. We analysed their symptoms, clinical signs, prehospital treatment, time lapsed before admission, time taken for symptomatic improvement and duration of hospital stay. We also categorized co-morbid conditions and outcomes. Variations in laboratory findings and chest X-ray abnormalities were discussed. Patients were followed up for three months for evidence of any residual disease and requirement of readmission. Restlessness is the most useful sign to pick up a case of H1N1 from other similar illnesses.